Determinan Kepuasan Kerja Perawat Melalui Stres Kerja - Muhammad Ridwan; Pahlawansyah Harahap; Sujito; Indarto; Ardiani Ika Sulistyawati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
This study aimd to empirically test and analyze the influence of the work environment, workload and communication on job satisfaction with work stress as an intervening variable with samples processed 132 nurses who worked at Permata Medika Hospital Semarang using the convenience sampling method. The analytical tool using PLS. The results of the validity test of all the indicators showed that there were no indicators that had to be dropped. The results of the reliability test showed that it reliable. The adjusted R square for the work stress is 97.300 per cent while the job satisfaction is of 89.200 per cent. The results of the direct effect test: that the work environment and workload have an effect on work stress, but communication has no effect on work stress. Then workload, communication and work stress are proven to have an effect on job satisfaction, but the work environment has no effect on job satisfaction.